2020
DOI: 10.1002/bse.2435
|View full text |Cite
|
Sign up to set email alerts
|

Predicting consumer adoption of branded subscription services: A prospect theory perspective

Abstract: Drivers of and barriers to consumer adoption of product‐service systems (PSS) deviating strongly from the current consumption paradigm remain unidentified. This study quantitatively investigates purchase intentions of a hypothetical branded fashion subscription service. This service features use‐ and result‐oriented PSS attributes in a lack of ownership, newness, and choice, and is investigated from a Prospect Theory perspective using a mixed method design combining an experiment with a survey (n = 524). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 82 publications
(216 reference statements)
2
23
0
1
Order By: Relevance
“…Risk is one of the factors that influence consumer decision making in choosing and buying a product. Several studies have found risk and trust have positive effects on purchase intention (Day et al, 2020;Hoque and Alam, 2018). This study confirmed the findings of Al-Ansi, Olya and Han (2019) which explained that health risk, psychological risk, quality risk, which are part of general risk, have a positive and significant impact on trust and intention to recommend halal food.…”
Section: Hypotheses Developmentsupporting
confidence: 88%
See 1 more Smart Citation
“…Risk is one of the factors that influence consumer decision making in choosing and buying a product. Several studies have found risk and trust have positive effects on purchase intention (Day et al, 2020;Hoque and Alam, 2018). This study confirmed the findings of Al-Ansi, Olya and Han (2019) which explained that health risk, psychological risk, quality risk, which are part of general risk, have a positive and significant impact on trust and intention to recommend halal food.…”
Section: Hypotheses Developmentsupporting
confidence: 88%
“…During Pandemic COVID-19 most consumers consider uncertain situation with relatively high health risk, so their final decision to buy or consume the product is based on the perceived advantage (Radic et al, 2021). Therefore, Prospect Theory is recommended and suitable to utilize in times of crisis with full of risk and uncertainty by using Health Risk, Psychological Risk, Quality Risk as the consumer consideration (Al-Ansi and Day et al, 2020). Most previous studies have used this prospect theory for the hospitality industry.…”
Section: Prospect Theorymentioning
confidence: 99%
“…One main difference is that in leasing, renting and sharing, products are used sequentially, while in pooling, products may be used simultaneously. The differences between the types are important when assessing environmental profiles of u-PSS, e.g., [32], as well as exploring their consumer acceptance [33]. In this study, we focus on leasing and renting and, because many companies use these terms interchangeably, we do as well.…”
Section: Characteristics Of Use-oriented Product-service Systemsmentioning
confidence: 99%
“…In the apparel sector, there have been several attempts to develop innovative BMs oriented towards sustainability, including rental and sharing systems (Adam et al, 2017; Camacho‐Otero et al, 2019; Day et al, 2020; Lang & Armstrong, 2018). The few LCA studies of these models indicate that they contribute to an overall reduction in environmental impacts (Bech et al, 2019; Piontek et al, 2020; Roos et al, 2015; Zamani et al, 2017).…”
Section: Methodsmentioning
confidence: 99%